Harmonious Labeling On Helm Graphs - Husnul Hatima; Nurdin Hinding; Muh Nur (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
graph  consists of two sets, namely vertices and edges , which are sets that cannot be empty. The helmet graph is obtained from graph circle with addition side pendants with notation . Something graph  side  is said to be harmonious if there is an injective function  that produces function labeling side  which will result in a different sided label. In this thesis, graphs with odd and even results will be constructed as  harmonious graphs. Where for every  for odd helmet graph and  for even helmet graph.